The Importance of Brand Identity for Environmental Conservation Brands - Killian, Sarah (The IIE, 2015)
The purpose of this research paper is to unpack how effectively environmental conservation companies position themselves within youth market. This paper aims to establish if environmental conservation companies appeal to younger children between the ages of 11 and 14. This will be done by looking at a case study of a South African environmental company, the Endangered Wildlife Trust, and analysing how they have constructed their brand identity to engage with the youth market. The Endangered Wildlife Trust, is a company that; ‘Is dedicated to conserving threatened species and ecosystems in Southern Africa to the benefit of all people’ (Endangered Wildlife Trust. 2015) This study is motivated by three research questions: (1) To determine how the Endangered Wildlife Trust has currently positioned their brand? (2) To establish how the youth market perceives the Endangered Wildlife Trust? (3) To evaluate the Endangered Wildlife Trust brand within the framework of Aaker’s brand identity model? The purpose of these questions is to establish solid information pertaining to the research problem. The research problem for this study is: To establish if there is a lack of environmental conservation companies brand identity amongst the Tween youth market in Johannesburg, between the ages of 11 and 14. The study has been conducted using Case Study qualitative research design. A field collection method will be used where focus groups will be conducted. The data findings will be analysed within Aaker’s Brand Identity Model. The significance of this research paper is that it could benefit environmental companies in creating strong brand identities. This study will give an indication as to how environmental conservation companies should be positioning their brands within the 11 to 14 year old market. The results of this study have been aligned with categories set out in Aaker’s brand identity model. The results indicate that, in certain areas of these categories, the Endangered Wildlife Trust is lacking when engaging with the Tween market. Recommendations have been included in this paper, if the brand at hand were to implement these recommendations; it could lead to a sustainable, life time relationship with the target market.
Keywords: Marketing; Branding; Eco-tourism; Youth